2020
DOI: 10.14715/cmb/2020.66.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Protein C and Protein S Levels in β-Thalassemia Major Patients in Erbil, Kurdistan Region

Abstract: Oxygen is transported in the blood through red blood cells and a protein called hemoglobin. The protein consists of two alpha and two beta chains.The lack of any of these chains is caused by the malfunction of the genes that produce them, and can lead to a genetic disease called thalassemia. In β-thalassemia, hemoglobin does not produce enough beta protein. According to mild to severe effects on the body, β-thalassemia is divided into three types minor, interstitial and major thalassemia. There are increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…One of the most recent complications in β-thalassemia patients is hypercoagulability, leading to severe morbidity and mortality [ 12 ]. This complication is not confined to β-thalassemia intermedia patients; activation of many hemostatic systems has also been demonstrated in persons with thalassemia major [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most recent complications in β-thalassemia patients is hypercoagulability, leading to severe morbidity and mortality [ 12 ]. This complication is not confined to β-thalassemia intermedia patients; activation of many hemostatic systems has also been demonstrated in persons with thalassemia major [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most recent complications in β-thalassemia patients is hypercoagulability, leading to severe morbidity and mortality [ 12 ]. This complication is not confined to β-thalassemia intermedia patients; activation of many hemostatic systems has also been demonstrated in persons with thalassemia major [ 12 14 ]. Even though transfusion and splenectomy ignorance are by far the most common causes of thalassemia, plenty of other causal variables have been proposed [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported conflicting results. Hadi et al reported that one of their patients with β-TM had a PC level of 140% [4]. In addition, although Eldor et al reported a significant decrease in PC and PS levels, but the levels of AT were within the normal reference range [19].…”
Section: Introductionmentioning
confidence: 97%
“…This imbalance between α and β chains leads to an excess of α chains and subsequently early destruction of the erythrocytes, resulting in anemia [1][2][3]. The estimated annual prevalence of symptomatic patients with β-thalassemia worldwide is 100,000 [3,4]. In Iran, the estimated incidence of thalassemia is around 3.6%, making the country one of the regions with a high prevalence of thalassemia [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation